2022
DOI: 10.1080/21645515.2022.2115267
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and acceptance of HPV vaccination for condyloma acuminata among men who have sex with men in China

Abstract: The dissemination of the fact that the human papillomavirus (HPV) vaccine can protect females as well as males is greatly beneficial for the control of condyloma acuminata (CA). We aimed to investigate the acceptance of the HPV vaccine for CA among men who have sex with men (MSM) in China. A cross-sectional online survey in the adult MSM population from 31 regions in China was carried out via WeChat in May 2017. Information on demographic characteristics, sexual behaviors, history of HIV and HPV infection, awa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Unfortunately, only 34.8% of the MSM in the study reported having friends or family members vaccinated. Notably, 85.1% of MSM from 31 regions in China expressed willingness to be vaccinated against CA [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, only 34.8% of the MSM in the study reported having friends or family members vaccinated. Notably, 85.1% of MSM from 31 regions in China expressed willingness to be vaccinated against CA [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the knowledge and attitude of individuals regarding HPV vaccine might be key factors in improving vaccination decisions. 11 , 37 , 38 …”
Section: Discussionmentioning
confidence: 99%
“…As of October 2020, 110 countries worldwide have implemented national HPV vaccination program [31,32]. At the population level, there is evidence of a reduction in highgrade cervical abnormalities among young women [33][34][35] and vaccination significantly reduces the prevalence of highrisk HPV types among young women [36].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in young women in their 20s-30s, it is predicted to prevent cervical cancer by approximately 7%-8% compared to the current vaccination program in 2036-2040. The nine-valent vaccine covers 5 additional HPV types (31,33,45,52, and 58) that cause cervical cancer. This provides 15%-20% additional coverage than bivalent or quadrivalent vaccines, thereby preventing 90% of the HPV types related to cervical cancer [39].…”
Section: Discussionmentioning
confidence: 99%